2020
DOI: 10.3928/02793695-20201013-02
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Patient Engagement Through Telepsychiatry: A Case Report Application

Abstract: The COVID-19 pandemic has changed psychopharmacological prescribing and management of patients around the world. Social distancing requirements led to a transition from face-to-face patient visits to telepsychiatry. Relaxed federal reimbursement policies during the COVID-19 pandemic expanded patient awareness and access to virtual care. For many psychiatric advanced practice RNs (APRNs), the transition to telepsychiatry was intended as a temporary solution until it is possible to return to in-person patient ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“… 2021 ). Many studies also reported staff working longer hours than usual (Johnson 2020 ), whether to cover staff absences (Liberati et al . 2021 ) or due to remote working, perturbing boundaries between work and home life (Nair et al .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 2021 ). Many studies also reported staff working longer hours than usual (Johnson 2020 ), whether to cover staff absences (Liberati et al . 2021 ) or due to remote working, perturbing boundaries between work and home life (Nair et al .…”
Section: Resultsmentioning
confidence: 99%
“…Increased staff shortages due to the COVID‐19 pandemic were also reported (Bae et al . 2022 ; Johnson 2020 ). Two additional studies reported increases in demand for services, including increased referral rates (Chemerynska et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations